Adaptive potential of patients with mental disorders - Maruta, Oksana (Psychological Counseling and Psychotherapy, 2020)
The work is devoted to studying the peculiarities of personal adaptive potential in mental disorders of different genesis. The analysis of the structure of adaptation potential, hierarchy of its elements, qualitative diversity of its internal and external relations can reflect the dynamics of adaptation process prognosis, be an effective component of psychological support programs in forming adaptive strategies of co-adaptive behavior, providing personalized psychological correction assistance. A total of 105 patients with mental disorders of various genesis aged 19 to 67 years participated in the study. Among them there were 35 patients with mental disorders of neurotic, 35 - endogenous, 35-with organic genesis. The comparison group consisted of 35 persons without signs of psychopathology. In case of mental disorders there is a decrease in personal adaptive potential. This reflects a reduction in the ability to respond adequately and productively to a complex of adverse factors under stressful loads, disproportionate use of functional reserves, which in turn affects the prevention of premorbid conditions. The structure of adaptation possibilities of patients with mental disorders testifies to the prevalence of neuropsychological stability as a leading adaptation mechanism in this category of patients, along with much less pronounced communication abilities and moral standards. Among patients with mental disorders of various genesis the highest adaptive potential was noted in the group of patients with organic disorders, which reflects their ability to adequately regulate the functional state of the organism in various living and activity conditions. Also this category of patients had the highest indices of neuropsychic resistance. Patients with neurotic disorders, as a leading way of adaptation, most often used communication skills, which prevailed in comparison with other nosological groups, and the lowest indicators for all components of coping behavior resources were observed in patients with endogenous disorders.